Antioxidant activity-guided isolation of usnic acid and diffractaic acid compounds from lichen genus Usnea sp. - Maulidiyah Maulidiyah, Akhmad Darmawan, Erviana Ahmad, Andi Musdalifah, Dwiprayogo Wibowo, La Ode Agus Salim, Zul Arham, Faizal Mustapa, Ishmah Farah Adiba Nurdin, Muhammad Nurdin (Journal of Applied Pharmaceutical Science, 2021)
The unique secondary metabolites from the lichen organism have been utilized as a raw material for producing natural medicine, which is very useful as an antioxidant (AO) agent. As we know, it also varies greatly depending on the surrounding environment. In this study, we explore the secondary metabolites from the lichen organism genus Usnea sp. originating from Southeast Sulawesi, Indonesia (tropical country), through an isolation procedure and its AO activity test. Based on the research results, the secondary metabolites from lichen Usnea sp. have been successfully isolated based on 1D-NMR spectroscopic interpretation, showing that the isolated compounds contain usnic acid (C18H16O7, yellow crystal) and diffractaic acid (C20H22O7, white crystal) in acetone extract. Moreover, the AO activity test using the 1,1-diphenyl-2-picryl-hydrazine method exhibits that diffractaic acid has quite an activity as AO agent, while usnic acid and acetone extract have provided the highest superoxide anion radical-scavenging activity as an AO agent. These chemical compounds are potentially used as a natural medicinal ingredient as an AO agent.
Keywords: Lichen, Usnea sp., usnic acid, diffractaic acid, antioxidant.